Evaluation of the Gastrointestinal Tract as Potential Route of Primary Polyomavirus Infection in Mice. - Gang Huang; Gang Zeng; Yuchen Huang; Bala Ramaswami; Parmjeet Randhawa (PLoS ONE)
Background Detection of Polyomavirus (PyV) DNA in metropolitan rivers worldwide has led to the suggestion that primary viral infection can occur by the oral route. The aim of this study was to test this notion experimentally. Methods Mouse PyV (MPyV) was used to infect C57BL/6J mice by the nasal or intragastric route. Viral load kinetics was studied 3, 7, 10, 14, 21 and 28 days post-infection (dpi) using quantitative PCR. Results Following nasal infection, MPyV DNA was readily detected in many organs including lung, heart, aorta, colon, and stool with viral loads in the range of 10(3)-10(6) copies/mg wet weight that peaked 7-10 dpi. Complete viral clearance occurred in the serum and kidney by 28 dpi, while clearance in other organs was partial with a 10-100 fold decrease in viral load. In contrast, following intragastric infection peak detection of PyV was delayed to 21 dpi, and viral loads were up to 3 logs lower. There was no detectable virus in the heart, colon, or stool. Conclusions The intragastric route of MPyV infection is successful, not as efficacious as the respiratory route, and associated with delayed viral dissemination as well as a lower peak MPyV load in individual organs.